Adsorption and Desorption of Tritium in Nuclear Graphite at 700°C: A Gas Chromatographic Study Using Hydrogen. (2nd September 2019) - Deng, Ke; Zhang, Mingjun; Wu, Xijun; Zhang, Qin; Yang, Guo; Ma, Zhaowei; Wei, Fei; Wang, Guanghua; Liu, Wei
Abstract: Because of its high content in irradiated nuclear graphite, tritium is treated as one of the most important radionuclides, and it should be carefully decontaminated before the final disposal of nuclear graphite. Tritium has similar chemical and physical characteristics to those of hydrogen; therefore, in this research, the adsorption and desorption of tritium in nuclear graphite using hydrogen were studied. Three kinds of nuclear graphite, IG-110, NBG-18, and NG-CT-10, were used to conduct adsorption and desorption experiments using a new method based on gas chromatography; subsequently, a first-principles calculation on graphene was carried out to simulate the desorption of hydrogen from graphite. The results showed that tritium can be weakly and strongly adsorbed in nuclear graphite. The differences found in the amount of weak adsorption within nuclear graphite were mainly due to the graphite's porosity and Brunauer-Emmett-Teller surface area, as reported previously in similar research. The mechanism for the strong adsorption was not explained clearly; it could be attributed to the results of a combination of the various physical properties of the graphite, especially the average pore size. The amount of weakly adsorbed hydrogen ranged from 48.4% to 95.2% of the total amount of adsorption for the nuclear graphite working at a temperature of 350°C. The weakly adsorbed tritium easily escaped from the nuclear graphite, indicating that this fraction of tritium would be the main source of pollution during the dismantling or the transportation of decommissioned graphite materials. In addition, the strongly adsorbed hydrogen began to be desorbed when the nuclear graphite was heated over 600°C, and 14% to 71% of the stably adsorbed hydrogen was desorbed when the temperature reached 700°C. A first-principles calculation indicated the activation energy for desorption of tritium from graphene to be about 2.17 eV.